Ups and Downs in Qatar-Israel Relations: A Constructivist Analysis of Wendt's â€œThree Cultures of Anarchyâ€ - Khair, Aulia ul (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This research conducts a constructivist analysis of Alexander Wendt's "three cultures of anarchy," using the case study of Qatar-Israel relations. It explores how Wendt's concept can be applied to examine the structure, roles, and cultural dynamics shaping the interactions between these two states through various phenomena and issues. The study reveals that the relationship between Qatar and Israel has experienced fluctuations. Initially, both countries shared a collective identity, facilitating interaction and problem-solving. However, shifts in domestic, regional, and international representations have rendered this identity less relevant over time. The research adopts qualitative methods and descriptive analysis, utilizing data from literature reviews, including books, journals, articles, and online sources. Grounded in a constructivist approach and Wendt's cultural theories, it examines international politics by identifying the evolution of cultural representations, logic, and internalization in state relationships. Findings indicate that the representations in Qatar-Israel relations are asymmetrical. While Israel perceives its friendship with Qatar as significant, Qatarâ€™s influence in the relationship remains limited. This study underscores the role of identity, culture, and representation in shaping interstate dynamics and offers insights into the complexities of their interactions.